(untitled) (CAHIERS MAGELLANES-NS, 2024)
Introduction: Artificial sweeteners are used as a substitute for regular sugar. The main purpose of using Artificial sweeteners is calorie reduction, as it is zero caloric. Recently, many studies have shown a relationship between artificial sweeteners and the increased risk of many diseases, such as cancer, heart disease, genotoxicity, etc. Objectives: The main objective of this study was to identify the level of knowledge among adults in Saudi Arabia about the side effects of artificial sweeteners. Methods: This is a cross-sectional study conducted in Saudi Arabia. The study’s population consisted of Saudi adults aged 18 and over. The minimum sample size to achieve a confidence level of 95% was 384. The Microsoft Excel program was used to design the data sheet and the SPSS program Version 27 for analysis by using descriptive parameters and Chi-Square test. Results: the total sample size were 403 participants, a significant majority of participants, 83%, reported being unaware of NNS. Meanwhile, 15.4% of respondents indicated being partly aware, while only 1.7% claimed to be fully aware. Regarding the relation between Knowledge and awareness of the side effects of artificial sweeteners and sociodemographic characteristics, Knowledge level of the side effects of artificial sweeteners revealed a statistically insignificant relation to gender, age, nationality and if participants have any comorbidities. Conclusion: The study revealed a significant lack of awareness among the participants, with the majority being unaware of non-nutritive sweeteners and their potential side effects. These findings indicate a knowledge gap that needs to be addressed, especially considering the conflicting evidence regarding the benefits and risks associated with artificial sweeteners.